Reviewers - Psicología, Actualidades (2021)
David Torres, Universidad de Iberoamérica, Costa Rica Edwin Salas Blas, Universidad de San Martín de Porres, Perú Iagor Brum Leitão, Federal University of Espírito Santo, Brasil Ana Paula Couto Zoltowski, Universidad Federal de Río Grande do Sul, Brasil Angelo Brandelli Costa, Pontificia Universidade Católica do Río Grande do Sul, Brasil Jonathan Peñalver González, Universidad Internacional de Valencia, España Esteban Montenegro Montenegro, Texas Tech University, Estados Unidos Ximeno Zacarías Salinas, Universidad de Colima, México Luis Diego Conejo, Universidad Nacional, Costa Rica Nicolás Ignacio Uribe Aramburo, Universidad de San Buenaventura, Colombia Juan Arias Castrillón, Universidad de San Buenaventura, Colombia José Antonio Ramos-Quiroga, Universitat Autònoma de Barcelona, España Lucía del Carmen Alba Pérez, Universidad de Ciencias Médicas de Villa Clara, Cuba Carmen Vizoso, Universidad de León, España Alejandra Alfaro Barquero, Instituto Tecnológico de Costa Rica, Costa Rica Tania Mondéjar Palomares, Universidad de Castilla La Mancha, España Tracy Sánchez, Universität Osnabrück, Alemania